Clinicopathological significance and potential drug targeting of CDH1 in lung cancer: a meta-analysis and literature review - Yu Q; Guo Q; Chen L; Liu S (Dove Medical Press, 2015)
Qiaowen Yu,1 Qisen Guo,2 Liangan Chen,3 Shuwei Liu1 1Shandong Provincial Key Laboratory of Mental Disorders, Research Center for Sectional and Imaging Anatomy, Shandong University School of Medicine, 2Respiratory Medicine, Shandong Cancer Hospital, Jinan, 3Department of Respiratory Diseases, People’s Liberation Army General Hospital, Beijing, People’s Republic of China Background: CDH1 is a protein encoded by the CDH1 gene in humans. Mutations in this gene are linked with several types of cancer. Loss of CDH1 function contributes to the progression of cancer by increasing proliferation, invasion, and/or metastasis. However, the association between and clinicopathological significance of CDH1 promoter methylation and lung cancer remains unclear. In this study, we systematically reviewed the studies of CDH1 promoter methylation and lung cancer, and evaluated the association between CDH1 promoter methylation and lung cancer using meta-analysis methods.Methods: A comprehensive search of the PubMed and Embase databases was performed up to July 2014. The methodological quality of the studies was also evaluated. The data were extracted and assessed by two reviewers independently. Analyses of pooled data were performed. Odds ratios (ORs) were calculated and summarized.Results: Finally, an analysis of 866 patients with non-small cell lung cancer from 13 eligible studies was performed. The CDH1 methylation level in the cancer group was significantly higher than in the controls (OR 3.89, 95% confidence interval [CI] 2.87–5.27, P<0.00001). However, there were no correlations between CDH1 promoter methylation and clinicopathological characteristics (sex status, OR 0.78, 95% CI 0.41–1.50, P=0.46; smoking history, OR 0.97, 95% CI 0.53–1.79, P=0.93; pathological type, OR 0.97, 95% CI 0.59–1.60, P=0.91; clinical staging, OR 1.48, 95% CI 0.81–2.68, P=0.2; lymph node metastasis, OR 0.68, 95% CI 0.13–3.63, P=0.65; or differentiation degree, OR 1.01, 95% CI 0.34–3.02, P=0.99).Conclusion: The results of this meta-analysis suggest that CDH1 methylation is associated with an increased risk of lung cancer. CDH1 hypermethylation, which induces inactivation of the CDH1 gene, plays an important role in carcinogenesis and may serve as a potential drug target in lung cancer. However, CDH1 methylation does not correlate with other factors, such as smoking history, clinical stage, pathological type, sex status, lymph node metastasis, or degree of differentiation. Keywords: CDH1, methylation, lung cancer, meta-analysis, tumor suppressor gene, odds ratio